Current Status of Biology–Biotechnic, Agronomic, and Biological Control of Rhynchophorus ferrugineus: A Review - Waqas Wakil; Maria C. Boukouvala; Nickolas G. Kavallieratos; Constantin S. Filintas; Nikoleta Eleftheriadou; Muhammad Usman Ghazanfar; Muhammad Yasin; Mirza Abdul Qayyum; Pasco B. Avery (Insects)
Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae), the red palm weevil (RPW), is a concealed voracious pest of different ornamental and economically important palm species, particularly the date palm. It can cause huge losses in ornamental and commercial palm plantations. RPW has spread rapidly from its original distribution in Southeast Asia to date palm-growing countries worldwide. It is now established in more than 50% of date palm-growing countries and 15% of the coconut-growing countries globally. To prevent further expansion of this pest, many countries have implemented strict legislative and quarantine measures surrounding the export of the palms plant genetic resources from RPW-infested countries. This review focuses on the general biology (life history, development), host range, geographical distribution, and management on the basis of biotechnic methods, farming practices, natural enemies, and important microbial control agents.